THE EFFECT OF GROIN MODIFICATION TO SHORELINE CHANGE IN SANUR BALI - Soni Senjaya Efendi (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2016)
Coastlines formed by beach filling and groin constructions in Sanur Beach have undergone changes for years. Erosion and loose of sand after beach filling still occur. Therefore, it is a need for evaluation of coastal structure performance. The methodology to be used in this study is by comparing coastline from numerical model with the result of measurement from year 2012. For declined coastline in area between groins, the treatment is done with shape modification of existing groin and addition of new coastal structure. There are three areas among groins that needed special treatment, GN.4 G7, G39 GA2, and G32 G37, which are identified by the model that has been calibrated with measurement data. Those three segments have greater coastline set back than others. In those three segments, the groins will be modified and new structure will be constructed. In GN.4 G7, a breakwater parallel with coastline will be added in the middle area between groins and the groin structure at GN4 will be modified from T shape to I shape. Groin GA2 will be straightened and new groin parallel with coastline will be constructed in between area G39 GA2. Meanwhile for G32 G37 segment, breakwater parallel with coastline will be added in the both sides of groin G32. From the model output, groin modification and addition of new structure make the coastlines setback decrease from 6,15 meter to 5,34 meter in GN4, from 3,4 meter to 2,85 meter in GA2, and from 3,69 meter to 2,98 meter in G32.